PENDAMPINGAN IBU HAMIL MELALUI PROGRAM ONE STUDENT ONE CLIENT (OSOC) DI WILAYAH KERJA PUSKESMAS GENUK SEMARANG - Apriliani Yulianti Wuriningsih; Sri Wahyuni; Tutik Rahayu; Hernandia Distinarista; Indra Tri Astuti; Nopi Nur Khasanah; Herry Susanto; Kurnia Wijayanti; Iskim Luthfa; Nutrisia Nu’im Haiya; Dyah Wiji Puspitasari (Universitas Muhammadiyah Semarang, 2017)
Maternity nursing is part of health services to improve women's health, one of them is high-risk pregnancies. OSOC Program is a program launched by the Central Java Government in an effort to decrease the high Maternal Mortality Rate (MMR) in Central Java based on the continuity of care approach. Direct learning experiences method was used in the community by placing students in each chosen area. Each student will get one client that he / she is managing during the learning experience. All clients in each region has supervisor, thus there was one student one client. There were 40 high risk pregnant women. After accompaniment, there was a significant result. Pregnant women took more than 90% Fe tablets since from the beginning of pregnancy, pregnant women and families prepared with birth planning and prevention of complications program, pregnant women and families who signed the delivery order from 85% up to 100%. Pregnant women who joined the pregnancy class rose from 75% to 100% after being accompanied by students. OSOC program can improve the welfare of mother and fetus. This program can be continued as the continuous basis by enhancing multisectoral further coordination.